BUDIDAYA JAMUR PERUSAK KAYU V. BUDIDAYA PLEUROTUS FLABELLATUS PADA ENAM JENIS KAYU - Sihati Suprapti; Ginuk Sumami (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Pink oyster mushroom (Pleurotus flabellatus) was cultivated on logs of six wood species, i.e. hamerang (Ficus grossularoides Burn.f.), jeungjing (Albizia falcataria (L.) Fosb.), jirak (Symplocos fasciculata Zoll.), kihuut (Vernonia arborea Ham.), manii (Maesopsis eminii Engl.) and seuseureuhan (Piper aduncum L.). The logs were kept slanted on an angle of ± 60° with bamboo supports in a house at Gunung Bunder Forest Complex, Bogor, The mature mushroom were harvested daily.The logs start producing fungus two months after inoculation. The average yield per log during one year observation was 581.8 g (hamerang,) 178.83g (manii), 69.23g (jeungjing), 25.47 g (kihuut), 19.44g (jirak), and 18.47 g (seuseureuhan).The average yield per month per m3 of log was obtained from hamerang 7.52 kg, man ii 1. 72 kg, jeungjing 0.58 6 kg, seuseureuhan 0.44 kg. jirak 0.321 kg and kihuut 0.244 kg.The total yield in one year observation was obtained from hamerang (90.20 kg), manii (20.67 kg), jeungjing (7.03 kg), seuseureuhan (5.3kg), jirak (3.85kg) and kihuut (2.93 kg) per m3 of log.